The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1999
DOI: 10.1152/jappl.1999.87.6.2207
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional model of the human airway tree

Abstract: A three-dimensional (3D) model of the human airway tree is proposed using a deterministic algorithm that can generate a branching duct system in an organ. The algorithm is based on two principles: 1) the amount of fluid delivery through a branch is proportional to the volume of the region it supplies; and 2) the terminal branches are arranged homogeneously within the organ. These principles define the basic process of branching: generation of the dimensions and directionality of two daughter branches is govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
212
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(218 citation statements)
references
References 25 publications
5
212
0
1
Order By: Relevance
“…One possibility is that the process is not precisely controlled, for example if branching occurs randomly to fill available space. Another is that control is precise but coding is simplified by repeated use of a branching mechanism, as in Mandelbrot's fractal model and other elegant algorithms [10][11][12][13][14][15][16][17] . Even with these attractive models and recent progress in identifying lung development genes 18 , understanding of the program that directs branching remains rudimentary.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that the process is not precisely controlled, for example if branching occurs randomly to fill available space. Another is that control is precise but coding is simplified by repeated use of a branching mechanism, as in Mandelbrot's fractal model and other elegant algorithms [10][11][12][13][14][15][16][17] . Even with these attractive models and recent progress in identifying lung development genes 18 , understanding of the program that directs branching remains rudimentary.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional branching patterns of the airways form a fractal structure, where each branch repeats itself over multiple length scales [7]. Power laws are closely related to fractals, and it can be shown that dynamic processes propagating from fractal structures also exhibit fluctuations in time that follow power law distributions [8].…”
Section: Introductionmentioning
confidence: 99%
“…The throat reproduces the model written in [7]. The geometry follows the models developed by Weibel [1] and Kitoaka et al [8]. The 3D numerical model has been made with the commercial code Ansys Gambit© [9].…”
Section: Methodsmentioning
confidence: 99%
“…The bifurcation angle was set to 35º according to the guidelines given in [1,8]. The geometry of the bifurcations in the bronchus at all the generations is created by a similar procedure.…”
Section: Methodsmentioning
confidence: 99%